PELATIHAN PENYUSUNAN INSTRUMEN KUESIONER UNTUK MENGUKUR VARIABEL ABSTRAK PADA GURU SMA/SMK DI KABUPATEN SUKABUMI, JAWA BARAT - Bagus Sumargo; Dania Siregar; Lukman El Hakim; Rizky Hilmianto; Danu Umbara (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Negeri Jakarta, 2024)
Abstract The quality of education in Kabupaten Sukabumi still poses serious challenges, as reflected in its Human Development Index (HDI) which is below the national average. One of the main causes is the lack of training for teachers, especially in developing instruments to measure abstract variables in students such as motivation, interest and attitude. This training aims to increase the capacity of SMA/SMK teachers in developing effective questionnaires to measure latent variables in students through lecture, question and answer, and simulation methods. The training evaluation was conducted using pre-test and post-test scores analyzed by Wilcoxon Signed Rank Test, showing a significant increase in participants' knowledge (p < 0.05). In addition, the results of the “Who Am I” questionnaire showed that most participants have an optimistic and confident personality, which supports learning and applying new knowledge. The training proved effective in improving teachers' competencies, with the majority of participants finding the training materials relevant and useful. Follow-up coaching is recommended to support further application and development of skills. Abstrak Kualitas pendidikan di Kabupaten Sukabumi masih menunjukkan tantangan serius, hal tersebut tercermin dari nilai Indeks Pembangunan Manusia (IPM) Kabupaten Sukabumi yang berada di bawah rata-rata nasional. Salah satu penyebab utamanya adalah karena kurangnya pelatihan bagi guru, terutama dalam menyusun instrumen untuk mengukur variabel abstrak dalam diri siswa seperti motivasi, minat, dan sikap siswa. Pelatihan ini bertujuan untuk meningkatkan kapasitas guru SMA/SMK dalam menyusun kuesioner yang efektif untuk mengukur variabel laten dalam diri siswa melalui metode ceramah, tanya jawab, dan simulasi. Evaluasi pelatihan dilakukan menggunakan skor pre-test dan post-test yang dianalisis dengan Uji Wilcoxon Signed Rank, menunjukkan peningkatan pengetahuan peserta secara signifikan (p < 0,05). Selain itu, hasil kuesioner